2022
DOI: 10.1123/ijspp.2021-0254
|View full text |Cite
|
Sign up to set email alerts
|

Upper-Limb Force–Time Characteristics Determine Serve Velocity in Competition Tennis Players

Abstract: Purpose: (1) To analyze the associations between serve velocity (SV) and various single-joint upper-limb isometric force–time curve parameters, (2) to develop a prediction model based on the relationship between these variables, and (3) to determine whether these factors are capable of discriminating between tennis players with different SV performances. Method: A total of 17 high-performance tennis players performed 8 isometric tests of joints and movements included in the serve kinetic chain (wrist and elbow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…16 Because of this, investigations have typically aimed at analyzing MIS values at specific joint angles observed throughout the kinetic chain, involving upper and lower body structures. Most of these studies concluded that the main contributor to a greater SV is shoulder internal rotation, 31,38 although positive relations were found between MIS and SV in most arm positions tested involved in the serve kinetic chain, 15,21,22 being the wrist flexion, extension, and shoulder flexion the movements with stronger associations. Notwithstanding, Baiget et al 21 considered these positive correlations present in specific positions and involving MIS of few muscle groups would not be a strong predictor of SV by themselves but only accounted for one piece of the puzzle.…”
Section: Strength Power and Rommentioning
confidence: 99%
See 2 more Smart Citations
“…16 Because of this, investigations have typically aimed at analyzing MIS values at specific joint angles observed throughout the kinetic chain, involving upper and lower body structures. Most of these studies concluded that the main contributor to a greater SV is shoulder internal rotation, 31,38 although positive relations were found between MIS and SV in most arm positions tested involved in the serve kinetic chain, 15,21,22 being the wrist flexion, extension, and shoulder flexion the movements with stronger associations. Notwithstanding, Baiget et al 21 considered these positive correlations present in specific positions and involving MIS of few muscle groups would not be a strong predictor of SV by themselves but only accounted for one piece of the puzzle.…”
Section: Strength Power and Rommentioning
confidence: 99%
“…Added to this, besides the combination of different joint positions and movements involved in the serve, certain strength levels regarding RFD and IMP may also positively influence SV. Baiget et al 22 investigated the influence of RFD at different time intervals (ie, 0-250 ms) alongside IMP on SV.…”
Section: Strength Power and Rommentioning
confidence: 99%
See 1 more Smart Citation
“…Tennis serve is a high-demanding coordinative technical action influenced by several biomechanical, anthropometric, or neuromuscular parameters (1,10,22). Alongside the recent evolution of tennis performance, the tennis serve has been considered the most powerful and important stroke in competition tennis players, with the serve velocity (SV) playing a preponderant role in elite tennis competitions (15) and also in young tennis players (29).…”
Section: Introductionmentioning
confidence: 99%
“…From a biomechanical standpoint, the serve is determined by diverse neuromuscular (e.g., rate of force development [RFD]), anthropometric (e.g., body mass and body height), or technical (e.g., ball impact angle and height) variables (1,18). Moreover, the activation and coordination of the trunk and upper-and lower-limb joints throughout the whole kinetic chain while relying on elastic energy and muscle preload is a paramount factor (21).…”
Section: Introductionmentioning
confidence: 99%